Increased size and cellularity of advanced atherosclerotic lesions in mice with endothelial overexpression of the human TRPC3 channel - Smedlund, Kathryn B. (2015)
In previous in vitro studies, we showed that Transient Receptor Potential Canonical 3 (TRPC3), a calcium-permeable, nonselective cation channel endowed with high constitutive function, is an obligatory component of the inflammatory signaling that controls expression of the vascular cell adhesion molecule-1 (VCAM-1) and monocyte adhesion to coronary artery endothelial cells. Also, TRPC3 expression in these cells was found to be up-regulated by proatherogenic factors, which enhanced inflammation and VCAM-1 expression. However, it remained to be determined whether these in vitro findings were of relevance to atherosclerotic lesion development in vivo. To answer this important question in the present work, we generated mice with endothelial-specific overexpression of human TRPC3 in an Apoe knockout background (TgEST3ApoeKO) and examined lesions in the aortic sinus following 10 and 16 wk on a high-fat diet. No significant differences were found in size or complexity of early stage lesions (10 wk). However, advanced plaques (16 wk) from TgEST3ApoeKO mice exhibited a significant increase in size and macrophage content compared with nontransgenic littermate controls. Remarkably, this change was correlated with increased VCAM-1 and phospho-IkBα immunoreactivity along the endothelial lining of lesions from transgenic animals compared with controls. These findings validate the in vivo relevance of previous in vitro findings and represent, to our knowledge, the first in vivo evidence for a proatherogenic role of endothelial TRPC3.